Perbedaan Diskolorisasi Resin Komposit Hybrid yang Direndam dengan Larutan Kopi Hitam dan Kopi Putih - Supiyana Supiyana; Atia Nurul Sidiqa; Novita Sukma (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
Hybrid composite resin absorbs water diffusion in the resin matrix so that it can undergo discoloration. Discoloration of the hybrid composite resin occur due to extrinsic factors, such as coffee. Coffee contains tannin that can cause discoloration of the hybrid composite resins through absorption and adsorption processes. The aims of this study to determine discoloration hybrid composite resin soaked with black coffee and white coffee solution. Sample is a hybrid composite resin diameter 15 mm and thickness 3 mm, 32 sample were divided into 2 groups. Standard color measurement using Dino - MicroscopeCapture 2.0. The mean value of the sample standard color of black coffee and white coffee before immersion greater than after immersion. Discoloration of differences before and after immersion in a black and white coffee ( p < 0.05 ) in both groups of hybrid composite resin samples. The test results between the two groups of hybrid composite resin samples were soaked in black and white coffee showed no difference.